PERCEPTION OF IMPACTED COMUNITY BY THE CONSTRUCTION OF DAMS IN PONOROGO AND PACITAN, EAST JAVA - Dian Suluh Kusuma Dewi; Dwiana Binti Yulianti; Ekapti Wahjuni Djuwitaningsih (Universitas Muhammadiyah Jember, 2020)
The aims of this study is to determine whether there are differences impacts and perception on the construction dams in the Ngindeng Village, Sawoo District, Ponorogo Regency and in Karanggede Village, Arjosari District, Pacitan Regenc. The dam construction sites are the location where they live before receiving relocation or compensation in the form of money. In addition, the researchers also looked for differences or similarities related to the socio-economic impacts for community in two different locations. This study used quantitative research methods. The total sample population taken in this study was 29 respondents from each place with a total sample of 58 respondents. Based on research conducted by researchers, it can be concluded that there are differences in perceptions between the people of Ngindeng Village and Karanggede Village, where in the instrument, Ho's perception was accepted and Ha was rejected. While indicators of the impact of development based on socio-economic instruments have the same answer between the people of Ngindeng Village and the people of Karanggede Village, where Ha is accepted and Ho is rejected.